Internal noise modelling problems of transport power equipment - Bazaras, Jonas (Transport, 2006)
The acoustic analysis of transport vehicles is presented in this article. Two types of vehicles of Russian production (TEP‐60 and M62) were selected for this research. Using ANSYS/Multiphysic software acoustic noise of different power units in the engine sector was simulated. In this paper we present the modelling results of the locomotive internal noise. In ANSYS/Multiphysic anbience the problems of acoustics are solved on the basis of harmonic response analysis by providing harmonic pressure excitation (sine type) at some points of fluid structure and obtaining the pressure distribution in the fluid. By changing the agitation frequency variable sound distribution at the interval of different frequencies is obtained. Constructing the calculation scheme for a three dimensional locomotive model, spatial structure of finite elements is used. The whole construction was described by 3D finite elements FLUID30 designed for a specified acoustic analysis. The presented acoustic calculation model of rolling‐stock cabin allows the evaluation of structural solutions and, in case of emergency, taking extra measures in the process of rolling‐stock design. The results of acoustic calculation were compared with experimental measurements.First Published Online: 27 Oct 2010